Assessment of prebiotic property of some Vietnam’s agro products and their applicability - Thu Huong, Dang; Huy Son, Dinh; La Anh, Nguyen (Vietnam Journal of Biotechnology, 2022)
In nature, prebiotics occur not only in fruits and vegetables but also in the seeds from fruits. This study focused on surveying the prebiotic property of the kernel fibers from eight Vietnam’s agro products which were jackfruit, avocado, rambutan, longan, durian, tropical almond, sesame, and lotus seeds. Kernels were investigated for total sugar, soluble protein, and fat contents. The highest total sugar content was found in lotus seed kernel (37.46%) but in kernels from sesame and tropical almond the value only was 2.42 and 3.07% respectively. Rambutan seeds had the highest fatty (54.3%) and soluble protein content (4.49%) while in kernel from durian had the lowest fatty (19.66%) and dissolved protein content (0.69%) among the studied seeds. Kernel powders were defatted, digested by enzymes: α – amylase, glucoamylase and neutrase, then extracted by 96% ethanol to obtain soluble fibers. The prebiotic potential of these fibers was investigated by the growth stimulation of four probiotic strains: Bifidobacterium animalis AP1.2, Bifidobacterium bifidum CNTP 6599, Lactobacillus casei PK2 and Lactobacillus fermentum SBV2. The highest increase of viable cells, compared to the control, was 0.52 lg (CFU/ml) found in medium supplemented with kernel fiber from longan, fermented by L. casei PK2. This fiber also stimulated the growth of four probiotics. However, the soluble fiber content obtained from longan seeds is the lowest among the types surveyed (0.02%). The fiber in jackfruit, avocado or lotus seeds also has a positive prebiotic index, except for L. fermentum SBV2, in which jackfruit and lotus seeds are still commonly used in Vietnamese life.